From theory to practice: operationalizing a climate vulnerability for sport organizations framework for heat hazards among US High schools. Issue 8 (August 2021) - Grundstein, Andrew J.; Scarneo-Miller, Samantha E.; Adams, William M.; Casa, Douglas J.
Abstract: Background: Sport organizations must comprehensively assess the degree to which their athletes are susceptible to exertional heat illnesses (i.e. vulnerable) to appropriately plan and adapt for heat-related hazards. Yet, no heat vulnerability framework has been applied in practice to guide decision making. Objectives: We quantify heat vulnerability of state-level requirements for health and safety standards affecting United States (US) high school athletes as a case study. Design: Observational. Methods: We utilize a newly developed climate vulnerability to sports organizations framework (CVSO), which considers the heat hazard of each state using summer maximum wet bulb globe temperature (WBGT) in combination with an 18-point heat safety scoring system (18 = best policy). Heat vulnerability is categorized as "problem" [higher heat (>27.9 °C) and lower policy score (≤9)], "fortified" [higher heat (>27.9 °C) and higher policy score (>9)], "responsive" [lower heat (<27.9 °C) and lower policy score (≤9)], and "proactive" [lower heat (<27.9 °C) and higher policy score (>9)]. Results: Across the US, the mean WBGT was 28.4 ± 2.4 °C and policy score was 6.9 ± 4.7. In combination, we observed organizations within each of the four vulnerability categories with 16% (n = 8) in fortified, 16% (n = 8) in proactive, 29% (n = 15) in problem, and 39% (n = 20) in responsive. Conclusions: The CSVO framework allowed us to identify different degrees of vulnerability among the state's and to highlight the 29% (n = 15) of states with immediate needs for policy revisions. We found the CSVO framework to be highly adaptable in our application, suggesting feasibility for use with other sports governing bodies.